A single-phase white-emitting La10(SiO4)6O3：Eu2+/Eu3+ phosphor for near-UV LED-based application. Issue 15 (15th October 2017) - Lu, Xue; Liu, Haitao; Yang, Xinyu; Tian, Yiguang; Gao, Xiaoli; Han, Liyuan; Xu, Qin
Abstract: A novel single-phase white-emitting phosphor La10 (SiO4 )6 O3 (LSO): xEu has been synthesized by high-temperature solid-state reaction. Its crystal structure, luminescence properties, fluorescence decay time and oxygen vacancies have been characterized by X-ray diffraction (XRD) and photoluminescence (PL) spectra. XRD result shows a typical oxyapatite structure with the space group of P6 3 /m . Characteristic excitation and emission peaks of Eu 2+ and Eu 3+ were observed from PL studies. The optimum doping concentration of Eu was found to be 7.5 mol% (x = 0.075). In this work, the lifetimes of Eu 3+ and Eu 2+ were considerably longer than those from some references. Under the excitation of different near ultraviolet ( n -UV) longer wavelengths ( λ ex = 360, 370, and 380 nm), the white light emission can be realized with the CIE chromaticity coordinates (0.3907, 0.3595), (0.3472, 0.3282), and (0.3504, 0.3062) for the phosphor LSO: 0.075Eu. The chromaticity coordinates of the phosphor were all located in the white region. Therefore, it is suggested that the explored LSO: 0.075Eu phosphor can be a good candidate for white light-emitting diodes (W-LEDs) application.